2012
DOI: 10.1016/j.biopsych.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness and Folding Deficits in Conduct-Disordered Adolescents

Abstract: Background Studies of pediatric conduct disorder (CD) have described frontal and temporal lobe structural abnormalities that parallel findings in antisocial adults. The purpose of this study was to examine previously unexplored cortical thickness and folding as markers for brain abnormalities in “pure CD”-diagnosed adolescents. Based on current fronto-temporal theories, we hypothesized that CD youth would have thinner cortex or less cortical folding in temporal and frontal lobes than control subjects. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
105
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 92 publications
15
105
5
Order By: Relevance
“…With respect to structural MRI, several studies have reported reduced amygdala volume in this population (17-20) though two did not (21, 22) . Moreover, cortical volume (17,19,23) and thickness (24) are more generally reduced within temporal cortex in youth with CD. There have also been reports of insula abnormalities–either when indexed by volume, (18-20) cortical thickness (25) or folding (24) —though this is not always seen.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…With respect to structural MRI, several studies have reported reduced amygdala volume in this population (17-20) though two did not (21, 22) . Moreover, cortical volume (17,19,23) and thickness (24) are more generally reduced within temporal cortex in youth with CD. There have also been reports of insula abnormalities–either when indexed by volume, (18-20) cortical thickness (25) or folding (24) —though this is not always seen.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cortical volume (17,19,23) and thickness (24) are more generally reduced within temporal cortex in youth with CD. There have also been reports of insula abnormalities–either when indexed by volume, (18-20) cortical thickness (25) or folding (24) —though this is not always seen. (21,22) Ventromedial prefrontal cortex reductions have also been reported—again either when indexed by volume, (17) cortical thickness (25) or folding (24) —though again this is not always seen (18-20,22) —one study reported increases in volume in this region.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations